ANALYSIS OF PARKING SPACE EFFECTIVENESS IN COMMERCIAL AREA JL. BOULEVARD AND JL. PENGAYOMAN, MAKASSAR CITY - Arinda Wahyuni; Ahmad Nadhil Edar; Gusti Hardyanti Musda (STEKOM PRESS, 2023)
From the results of previous studies in the commercial area of Jl. Boulevard and Jl. Pengayoman is almost never empty of illegal parking for four-wheeled vehicles, generally, four-wheeled parking is lined up in the middle of the road, usually during the day, illegal parking is almost crowded starting from the gate of Jl Boulevard, near Jl. AP. Pettarani, to the front of Panakkukang Mall Panakkukang. Meanwhile, the shelter also starts from the gate of protection to the old adhiyaksa quarters. Where along the protection road there are many retail shops and offices so that it makes parking lots up to the pedestrians and the shoulders of the road. This is what causes the loss of user comfort and the changing function of pedestrians in the Jl. Boulevard and Jl. Protection so that it is an act that is contrary to Islamic law which is unlawful because it is illegal, does not comply with regional law and also harms other people. So to restore the comfort and function of existing pedestrians in the commercial area of Jl. Boulevard and Jl. Pengayoman, so we raised a research theme entitled “Analysis of the Effectiveness of Parking Spaces in Commercial Areas Jl. Boulevard and Jl. Pengayoman Kota Makassar” We examine this to find out the causes of illegal parking for visitors to the commercial area on Jl. Boulevard and Jl Pengayoman Makassar City. The research variable is the effectiveness of parking spaces in the Jl. Boulevard and Jl. Protection. Data analysis used qualitative or descriptive analysis which was used to explain the results of interviews with informants and observations conducted on Jl. Boulevard and Jl. Pengayoman City of Makassar with the results of a literature review on the effectiveness of parking spaces. from the results of the research we conducted, overall the effectiveness of existing parking provision and services is still not effective. This is caused by The existing parking facilities do not meet the parking space standard (SRP), where the average parking area for commercial buildings (shops) on Jalan Boulevard and Jalan Pengayoman is 40m2, while the parking space standard is according to the Decree of the Director General of Hubda No: 272 /HK.105/DRJD/96 is 90 (1), and the results of interviews with respondents who use parking spaces in the Commercial Area Jalan Boulevard and Jalan Pengayoman on average answer the ineffectiveness of parking spaces in the Commercial Area Jalan Boulevard and Jalan Pengayoman based on the questions asked in assessing the level of effectiveness of parking spaces. Keywords: Effectiveness, Parking Space, Convenience